The development of the sheep farming business in Tempursari Village, Magelang Regency, through the green economy-based revolving livestock concept - Retno Rusdjijati; Agus Suprapto; Veni Soraya Dewi (Community Empowerment, 2023)
One of the untapped potentials in Tempursari Village, Candimulyo District, Magelang Regency, lies in the sheep farming business. However, this endeavor has yet to reach its optimal potential due to the limited knowledge of breeders regarding sheep farming and marketing. To address this, mentoring activities were initiated for breeders in Tempursari Village, aiming to optimize their businesses through a green economy-based revolving livestock concept. The mentoring process commenced with a Focus Group Discussion (FGD) involving four current breeders and two prospective breeders. This session delved into a comprehensive analysis of the challenges faced and the aspirations for business development. As a result, a sheep farming group named 'Migunani' was established. The breeders received education on effective sheep farming practices and determining appropriate product sales prices. The mentoring activities concluded with the provision of assistance, which included ten 12-month-old sheep and seeds for fodder plants such as bb biogen, red napier, and pakchong, each comprising 300 stems. Supplying fodder plant seeds aims to enable farmers to cultivate their own feed, eliminating the need to graze elsewhere to meet the dietary requirements of the sheep.